Alien rule - Hechter, Michael (New York : Cambridge University Press, 2013)
"This book argues that alien rule can become legitimate to the degree that it provides governance that is both effective and fair. Governance is effective to the degree that citizens have access to an expanding economy and an ample supply of culturally appropriate collective goods. Governance is fair to the degree that rulers act according to the strictures of procedural justice. These twin conditions help account for the legitimation of alien rulers in organizations of markedly different scale. The book applies these principles to the legitimation of alien rulers in states (the Republic of Genoa, nineteenth- and twentieth-century China, and modern Iraq), colonies (Taiwan and Korea under Japanese rule), and occupation regimes, as well as in less encompassing organizations such as universities (academic receivership), corporations (mergers and acquisitions), and stepfamilies. Finally, it speculates about the possibility of an international market in governance services"--
Machine generated contents note: 1. Introduction; 2. Alien rule and its discontents; 3. The failure of legitimate rule in Iraq; 4. Resistance to alien rule in Taiwan and Korea; 5. Dynamics of military occupation; 6 Academic receivership as alien rule Gail Dubrow and Debra Friedman; 7. Conclusion.
Includes bibliographical references and index.
Keywords: Imperialism -- Case studies; Legitimacy of governments -- Case studies; Military occupation -- Case studies; Sovereignty -- Case studies